The Effect Of Moringa Leaf Extract On Hyperglycemic Rat Liver Function - Wulan Christijanti; Aditya Marianti; R. Susanti; Senda Kartika Rakainsa (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
One of the management of diabetics is to maintain stable glucose levels. Often diabetes treatment combines chemical drugs with medicinal plants. People have consumed a lot of Moringa leaves which are believed to be able to maintain body condition. One of the benefits of Moringa leaves with phytochemical components in it is as a hepatoprotector. The aim of this study was to analyze the role of Moringa leaf extract on liver function parameters of hyperglycemic rats. There were 4 groups, normal control (K0), hyperglycemic rats with induction of alloxan 125 mg/kg bw and divided into three groups treated with moringa leaf extract at a dose of 0 mg (K1), 200 mg (T1) and 400 mg/kg bw (T2 ) for 21 days. The variables measured were aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels, total cholesterol. Data were analyzed with Anova P0.05 and Least Significance Different (LSD) follow-up test. The results showed that the levels of AST and ALT were highest in the K1 group which then decreased significantly in the group that received Moringa extract (T1 and T2). Statistically there was a significant difference (p0.05) between the control and treatment groups. Cholesterol levels in the control group were significantly lower than the diabetes and treatment groups, but there was no significant difference between the treatment groups. The conclusion is that Moringa leaf extract has an effect on reducing liver enzyme levels and cholesterol in hyperglycemic rats. This research adds to the study of the hepatoprotective potential of Moringa leaf extract in hyperglycemic rats.